Is progressive early digit mobilization intervention beneficial for patients with external fixation of distal radius fracture? A pilot randomized controlled trial. (November 2013) - Kuo, Li-Chieh; Yang, Tai-Hua; Hsu, Ying-Ya; Wu, Po-Ting; Lin, Cheng-Li; Hsu, Hsiu-Yun; Jou, I-Ming
Objective: To investigate whether progressive early digit mobilization resulted in better outcomes for hand stiffness and related functional results, as well as the effects on the bone healing process. Design: Prospective, pilot randomized controlled trial. Setting: A university hospital in southern Taiwan. Participants: Twenty-two patients with distal radius fracture randomized into two groups: early digit mobilization or control. Interventions: The intervention group received 45 minutes per treatment session and three sessions per week until the external fixator was removed 6 weeks after fracture. The control group received usual home programmes. After removing fixators, both groups received regular rehabilitation programmes until 12 weeks after surgery. Main measures: Hand strength, dexterity and functional outcomes were obtained using a dynamometer, Purdue pegboard and self-report assessment, respectively, and X-rays of the distal radius were taken to reveal bone healing 1, 3, 6 and 12 weeks after surgery. A motion tracking system measured various kinematic parameters. Results: The recovery rates between the groups showed statistically significant differences in both thumb workspace (81.55% vs. 69.54%, P = 0.04) and finger workspace (89.22% vs. 59.97%, P = 0.03) 12 weeks after injury. However, no statistical differences were found in finger dexterity, strength and self-reported outcomes. The radiographic assessment showed no significant differences between the groups for radial inclination, radial height and volar tilt throughout the examinations. Conclusions: The findings suggest that early rehabilitative intervention for digits is applicable for distal radius fracture treatment, and does not produce additional bone deformities.